2012
DOI: 10.1590/s0102-33062012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in morphological and physiological leaf characteristics between Tabebuia aurea and T. impetiginosa is related to their typical habitats of occurrence

Abstract: Recebido em 18/08/2011. Aceito em 16/04/2012 RESUMO (Diferenças em características morfológicas e fisiológicas foliares entre Tabebuia aurea e T. impetiginosa estão relacionadas aos seus ambientes típicos de ocorrência). Tabebuia é um gênero representativo do bioma Cerrado, ocorrendo em formações savânicas e florestais, que diferem em termos de microclima, disponibilidade hídrica e propriedades do solo. Neste trabalho foi realizado um estudo comparativo de parâmetros morfológicos e fisiológicos entre duas espé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
15
0
3
Order By: Relevance
“…Studies focusing on variations in the physiological attributes of plants according to environmental conditions have been performed with a number of species (Boardman 1977;Chazdon 1986;Chen and Klinka 1997;Murchie and Horton 1997;Naramoto et al 2006;Sinclair et al 2008;Rodríguez-Garcia and Bravo 2013;Rossatto et al 2013;Puglielli et al 2015;Vieira et al 2015;Vitória et al 2016) and have demonstrated that populations established in environments with high solar irradiation have thicker leaves, with higher rates of gas exchange. Studies of morphofunctional traits have examined leaf renewal, leaf age, and wood density associated with habitat heterogeneity (Goulart et al 2005;Lemos Filho et al 2008;Toledo et al 2012;Capuzzo et al 2012). Attributes such as phenology, leaf age, gas exchange, photosynthetic pigments, water potential, wood density, and leaf morphological attributes (thicknesses, succulence, density, and leaf mass per area) have been correlated with environmental conditions such as irradiance, VPD, and water balance (Rosado and de Mattos 2007;Meinzer et al 2009;Rosado et al 2013;Rossatto et al 2013;Braga et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on variations in the physiological attributes of plants according to environmental conditions have been performed with a number of species (Boardman 1977;Chazdon 1986;Chen and Klinka 1997;Murchie and Horton 1997;Naramoto et al 2006;Sinclair et al 2008;Rodríguez-Garcia and Bravo 2013;Rossatto et al 2013;Puglielli et al 2015;Vieira et al 2015;Vitória et al 2016) and have demonstrated that populations established in environments with high solar irradiation have thicker leaves, with higher rates of gas exchange. Studies of morphofunctional traits have examined leaf renewal, leaf age, and wood density associated with habitat heterogeneity (Goulart et al 2005;Lemos Filho et al 2008;Toledo et al 2012;Capuzzo et al 2012). Attributes such as phenology, leaf age, gas exchange, photosynthetic pigments, water potential, wood density, and leaf morphological attributes (thicknesses, succulence, density, and leaf mass per area) have been correlated with environmental conditions such as irradiance, VPD, and water balance (Rosado and de Mattos 2007;Meinzer et al 2009;Rosado et al 2013;Rossatto et al 2013;Braga et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great increase in SLA in 95% shade, there was not an effective increase in L A . The lower SLA in critical shade levels is a less flexible trait that is characteristic of plants adapted only to the higher irradiances of the savannas [2,62]. The present study demonstrates that E. contortisiliquum, although classified as a pioneer and adapted to high irradiances, displayed larger SLA in shade, a trait that if expressed at the right moment may positively influence L A and shade tolerance.…”
Section: Growth and Physiological Morphological And Anatomical Adjumentioning
confidence: 47%
“…& Hook. f. ex S. Moore-a pioneer tree characteristic of the savanna domain [62]-suffered a reduction in its S D and L A in 70% and 95% shade compared to full sun and 50% shade in 70-day-old seedlings [63]. In fact, the lower L A of T. aurea was influenced by a low SLA in 70% shade.…”
Section: Growth and Physiological Morphological And Anatomical Adjumentioning
confidence: 98%
“…Wood density was chosen based on different tree species (see Table 1), while leaf density was taken as the mean value of 0.41 g·cm −3 [25,26]. The biomass of these individual components was assessed with values calculated using allometric equations developed by [27].…”
Section: Individual Tree Biomass Estimation Using a Reconstructed Trementioning
confidence: 99%